US balance sheet policy and international capital flows empirical evidence from emerging markets - Ramaloo Malarvily; Lee, Hock Ann (Academic Inspired Network, 2022)
This paper examines the effect of United States balance sheet policy on different type of capital flows- that is, bond vs equity flows. Panel data approaches were employed to study the determinants of bond and equity flows in emerging market economies (EMEs) namely, Argentina, Brazil, Chile, Mexico, China, India, Indonesia, Malaysia, Philippines, South Korea, and Thailand, over the January 2008 – April 2019 period. This research found that the US unconventional monetary policy has a significant impact on the types of capital flows in emerging markets that are most vulnerable to the changes in the Fed’s balance sheet. However, the determinants of flows can significantly be different across types of flows measured, bond or equity. For the bond flows, the 10-year government bond yield, US balance sheet policy and global risks have a statistically significant impact on capital flows to EMEs. Whereas, for the equity flows, the global risks and federal fund rate have a statistically significant impact on capital flows to EMEs. We found that the bond and equity flows are attributed by different factors. The empirical results from this research could assist the policymakers in crafting relevant policies associated with capital inflows in their respective countries.